'Bright, shiny, inconsequential'? The rise and fall of innovation labs in the aid sector. Issue 2 (1st February 2023) - Wells, Tamas
Abstract: Within the humanitarian and development sectors over the last 15 years, innovation 'labs', 'units', 'spaces' and 'exchanges' have become immensely popular. Yet while hundreds of labs have been formed by non-government organisations, United Nations agencies and bilateral and multilateral agencies, many have now been dissolved. Why did leaders in the humanitarian and development sectors so strongly advocate for creation of labs, and then so quickly abandon them? There has been a surprising lack of scholarship, and particularly empirical studies, on the phenomenon of innovation labs in the aid sector. This article draws on the wider public sector innovation lab literature and a case study of the Innovation Space, a lab within a wider aid agency. It argues that the context of bureaucratic culture and political patronage, and innovation as a 'magic concept', contributed to both the appeal and vulnerability of the Innovation Space, an initiative that was ultimately dissolved. In dismissing innovation labs in the aid sector as simply 'bright, shiny, and inconsequential' experiments, however, scholars and practitioners risk overlooking the deeper ideologies within innovation thinking in the aid sector that the rise and fall of labs reveals.